2016
DOI: 10.1007/s10964-016-0594-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and Conscientiousness as Moderators of the Relation Between Social Withdrawal and Internalizing Problems in Adolescence

Abstract: Social withdrawal, or refraining from social interaction in the presence of peers, places adolescents at risk of developing emotional problems like anxiety and depression. The personality traits of neuroticism and conscientiousness also relate to emotional difficulties. For example, high conscientiousness predicts lower incidence of anxiety disorders and depression, while high neuroticism relates to greater likelihood of these problems. Based on these associations, socially withdrawn adolescents high in consci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 52 publications
(85 reference statements)
8
35
0
3
Order By: Relevance
“…Multiple regression revealed that increasing dispersion of the fear/violence cluster was linked to increasing Neuroticism and decreasing Conscientiousness (see also Supplementary Table 5). Such an opposite relationship between these two personality dimensions is not entirely unexpected, as it has been reported as a general finding when assessing the Big Five personality factors (Costa et al, 1991), linked to mental disorders (Trull and Sher, 1994;Kotov et al, 2010), and tied to such domains as social media activity (Liu et al, 2016), emotional problems in adolescents (Smith et al, 2017), and even physiological mechanisms of inflammation (Sutin et al, 2010). Regarding Neuroticism, it is possible that higher Neuroticism coincides with a greater differentiation in the processing of negative stimuli, thereby leading to a finer-grained categorization (i.e., a more dispersed clustering) of negative information.…”
Section: Discussionmentioning
confidence: 71%
“…Multiple regression revealed that increasing dispersion of the fear/violence cluster was linked to increasing Neuroticism and decreasing Conscientiousness (see also Supplementary Table 5). Such an opposite relationship between these two personality dimensions is not entirely unexpected, as it has been reported as a general finding when assessing the Big Five personality factors (Costa et al, 1991), linked to mental disorders (Trull and Sher, 1994;Kotov et al, 2010), and tied to such domains as social media activity (Liu et al, 2016), emotional problems in adolescents (Smith et al, 2017), and even physiological mechanisms of inflammation (Sutin et al, 2010). Regarding Neuroticism, it is possible that higher Neuroticism coincides with a greater differentiation in the processing of negative stimuli, thereby leading to a finer-grained categorization (i.e., a more dispersed clustering) of negative information.…”
Section: Discussionmentioning
confidence: 71%
“…Differing from conscientiousness, neuroticism was the only personality trait linked to less PSS. Individuals who are higher in neuroticism may choose to withdraw from social interactions because of anxiety (Smith et al, 2017). Contrary, extraversion was linked to more PSS and less functional limitations.…”
Section: Personality Perceived Social Support and Functional Limitamentioning
confidence: 93%
“…For example, individuals scoring higher in neuroticism are often depressed or anxious, which makes them more likely to withdraw from social situations (Bowling, et al, 2005). Therefore, individuals who are higher in neuroticism likely experience less social interaction, including PSS, which can be especially challenging over long periods of time (Smith, Barstead, & Rubin, 2017). Contrary to neuroticism, individuals higher in conscientiousness or extraversion were less likely to withdraw from their social network even when dealing with depression because of the propensity to uphold responsibility in their relationships (Cukrowicz et al, 2008).…”
Section: Personality and Perceived Social Supportmentioning
confidence: 99%
See 2 more Smart Citations